Determinant Factors Poverty of Relativity in Banten Province: A Panel Data Analysis - Deris Desmawan; Rizal Syaifudin; Randi Mamola Mamola; Hanifa Haya; Dwi Indriyani (Ecoplan, 2021)
The problem of the poverty of relativity today is still a crucial topic considering the economic conditions in Indonesia are experiencing a slump due to Covid-19. The problem of poverty relativity is one of the main points that must be faced by the government in providing social protection assistance policies as a form of economic recovery during the Covid-19. The poverty of relativity in Banten Province is relatively high even though it has been ranked 10 nationally. Therefore, this study aims to analyze the relationship between unemployment, income inequality, and human capital as well as find out which level is very dominant in the long run on each of the variables that directly affect the relativity of poverty in Banten Province. This study examines how changes in economic indicators occur due to the Covid-19 pandemic in 8 Regencies/Cities of Banten Province. The analysis of this study uses panel data regression using the method Fixed Effect Model (FEM) in 8 regencies/cities in Banten Province in the data range from 2016 to 2020. The results of this study indicate that unemployment due to layoffs has a positive and significant influence on the relativity of poverty in 8 districts/cities of Banten Province. Furthermore, this study shows that income inequality has no significant and positive effect on the relativity of poverty. Meanwhile, human capital appears to be one of the dominant factors that can have a negative and significant impact on economic recovery and reduce the relative impact of poverty during the Covid-19 pandemic.